(untitled) (Global Journal of Management and Business Research, 2013)
The article aims in analyzing the maturity level of the organizational process in a centennial company of the welding sector in the State of Minas Gerais, Brazil. The Theoretical Framework emphasizes the concepts of Organizational Processes and Maturity Process. The model developed by Michel Hammer -Process Enterprise Maturity Model (PEMM) -was the basis for analyzing the processes’ performance. Data analysis was based on semi-structured interviews. Interviewees expressed their views, values and personal views to all the questions that were asked. Despite being a global and centennial company, there is still a long way to achieve the desired levels of excellence, even that the processes are reliable and stable.